Copper(ii) bromide-catalyzed intramolecular decarboxylative functionalization to form a C(sp3)–O bond for the synthesis of furo[3, 2-c]coumarins1. Issue 12 (28th March 2015) - Zhang, W. L.; Yue, S. N.; Shen, Y. M.; Hu, H. Y.; Meng, Q.-H.; Wu, H.; Liu, Y.
<x xml:space="preserve">Abstract</x> Copper(ii) bromide-catalyzed intramolecular decarboxylative functionalization to form a C(sp3)–O bond has been developed.